MgAl-LDH-biochar composites as a green sorbent for lead removal from water - Idan, Intidhar J.; Al-Rifaie, Jawad K.; Ewadh, Hind M. (Scientific Review Engineering and Environmental Sciences (SREES), 2021)
The present study aims at the development of a green sorbent (MgAl-LDH-biochar) from the municipal solid wastes (cow bones) to remediate water from heavy metals. MgAl-LDH-biochar was characterized using X-ray diffraction (XRD), and it was used to remove lead at different pH, doses, contact time (Ct), and solution temperatures (St). The obtained results proved MgAl-LDH-biochar removes 99% of lead when the initial pH, Ct, St, and dose were 5.0, 80 min, 45°C, and 0.2 g·L–1, respectively.